Observer design for simultaneous robust actuator and sensor faults reconstruction - Ben Brahim, Ali; Dhahri, Slim; Ben Hmida, Faycal; Sellami, Anis (2015 16th International Conference on Sciences and Techniques of Automatic Control and Computer Engineering (STA), 2015)
This paper describes a robust fault reconstruction and estimation design for a class of nonlinear system described by Takagi-Sugeno structure subject to faults affecting actuators, sensor faults and disturbances. The premise variables are assumed to be unmeasurable. The main innovation is focused primarily to conceive Sliding Mode Observer (SMO) designed to compensate faults behaviors from the system states estimation. In formalism of multi-objective optimisation, we derive sufficient conditions to guarantee the states estimation error stability and to obtain the observer gains. Simulation result is given to evaluate the proposed approach performances.